2015
DOI: 10.1177/2168479014539152
|View full text |Cite
|
Sign up to set email alerts
|

Inferences Beyond a Study Design’s Grasp: A Cautionary Case Study From the Recent Renal Sympathetic Denervation Literature

Abstract: During the past 6 years, the technique of renal sympathetic denervation has been proposed as a treatment for drug-resistant hypertension, and several studies have been published that claimed to provide supportive evidence of its efficacy. There is no question that resistant hypertension is a major medical concern: hypertension has been authoritatively designated as the greatest threat to the global burden of disease, and approximately 8% of hypertensive individuals have resistant hypertension. However, the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, that initial optimism was short‐lived given the recent failure of the SYMPLICITY HTN‐3 trial to meet both primary and secondary efficacy endpoints. That SYMPLICITY HTN‐3 was the first RDN study to employ a sham‐procedure control group suggested that study design limitations may have been responsible for the apparently positive results of SYMPLICITY HTN‐1 and HTN‐2 . As the scientific community continues to digest the results of SYMPLICITY HTN‐3, subsequent post hoc analyses have identified multiple potential confounding factors emergent from this study's design as well .…”
Section: A Brief History Of Rdn Researchmentioning
confidence: 95%
See 1 more Smart Citation
“…However, that initial optimism was short‐lived given the recent failure of the SYMPLICITY HTN‐3 trial to meet both primary and secondary efficacy endpoints. That SYMPLICITY HTN‐3 was the first RDN study to employ a sham‐procedure control group suggested that study design limitations may have been responsible for the apparently positive results of SYMPLICITY HTN‐1 and HTN‐2 . As the scientific community continues to digest the results of SYMPLICITY HTN‐3, subsequent post hoc analyses have identified multiple potential confounding factors emergent from this study's design as well .…”
Section: A Brief History Of Rdn Researchmentioning
confidence: 95%
“…Percutaneous RDN is a procedure in which radiofrequency energy is applied with an endovascular catheter inserted via the femoral artery to both renal arteries sequentially, with resultant ablation of the sympathetic nerve fibers . The rationale for targeting these nerve fibers is derived from seminal observations that in hypertensive states there is a “persistent and adverse activation of sympathetic outflows to the heart and kidneys.” Indeed, the apparent early success of RDN in the SYMPLICITY HTN‐1 and SYMPLICITY HTN‐2 trials led to growing support of the persistent sympathetic outflow hypothesis and advocacy for RDN among clinicians.…”
Section: A Brief History Of Rdn Researchmentioning
confidence: 99%
“…The results were widely regarded as compelling evidence that the procedure was both safe and effective. However, despite the proclamations of conclusiveness of these results in a large number of publications (the majority of which were review‐type papers, not empirical study reports), these studies were not methodologically designed to support such claims, ie, Symplicity HTN‐1 did not include a control group and Symplicity HTN‐2 did not utilize a sham‐control group (see also additional references). Subsequent negative results from Symplicity HTN‐3, the most rigorously designed study to date, as was appropriate for its stage of development (phase 3), not only failed to provide supportive evidence of the intervention's efficacy but also demonstrated why scientific rigor in study design is critical for informing decisional benefit‐risk assessments even in the presence of vocal and broad‐based expert scientific endorsement.…”
Section: Resistant Hypertension and Renal Sympathetic Denervationmentioning
confidence: 99%
“…Turner and O'Brien noted that, by writing in the voice of his beloved character Sherlock Holmes, Sir Arthur Conan Doyle was able to wryly observe that it is a huge mistake to theorize before one has acquired the data, since to do so inevitably leads one to twist facts to suit theories rather than developing theories to suit facts. With the recent guidance from leading US and European investigators, it now appears that we have good road maps to guide the acquisition of appropriately informative data and more authoritatively determine whether RDN is likely to be a useful clinical intervention for certain prospectively identifiable individuals with RH.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Second, I had been critical of safety-related nomenclature used in a multitude of reviews and commentaries addressing earlier trials of renal sympathetic denervation, and also critical of efficacy claims made in the broad literature based on studies (SYMPLICITY HTN-1 2 and SYMPLICITY HTN-2 3 ) whose designs did not legitimately permit such claims. 4,5 SPYRAL HTN-OFF MED’s design 6 had the inherent ability to permit the claims of efficacy made in this case, and I was pleased to see that the nomenclature used in the reporting of safety issues was conservative and appropriate. After first providing some context, this Editorial summarizes the results presented, and also represents a plea for those writing (or about to write) journal articles addressing the latest developments in this field to avoid using the single, emphatic descriptor “safe.”…”
mentioning
confidence: 99%